2002
DOI: 10.1093/ajcn/76.5.1023
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between the effect of carbohydrates on blood glucose and subsequent short-term food intake in young men,,

Abstract: Food intake and subjective appetite are inversely associated with blood glucose response in the 60 min after consumption of carbohydrates. Carbohydrates with a high glycemic index (glucose, polycose, and sucrose) suppress subjective appetite and food intake in the short term, but those with a low glycemic index (amylose and amylopectin) do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
185
5
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(211 citation statements)
references
References 29 publications
19
185
5
2
Order By: Relevance
“…A study investigating the effects of dietary GI and glycaemic load on energy metabolism and voluntary food intake in obese children showed that high-GI meals elicit a sequence of hormonal changes that might limit the availability of metabolic fuels and cause overeating in children (Ludwig et al, 1999). An increase in postpandial satiety by consuming lower dietary GI has been reported in some related studies (Ball et al, 2003;Warren et al, 2003;Alvina and Araya, 2004), while another study reported an inverse relationship between appetite and postprandial blood glucose response (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…A study investigating the effects of dietary GI and glycaemic load on energy metabolism and voluntary food intake in obese children showed that high-GI meals elicit a sequence of hormonal changes that might limit the availability of metabolic fuels and cause overeating in children (Ludwig et al, 1999). An increase in postpandial satiety by consuming lower dietary GI has been reported in some related studies (Ball et al, 2003;Warren et al, 2003;Alvina and Araya, 2004), while another study reported an inverse relationship between appetite and postprandial blood glucose response (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 71%
“…Ball et al (2003) demonstrated a prolongation of satiety following an intervention with a low-GI meal replacement, while Alvina and Araya (2004) observed significantly less satiety in obese children after consumption of a carbohydrate meal with a rapid digestion rate. Although some studies did not suggest an increase postprandial satiety by increasing dietary GI (Heini et al, 1998;Anderson et al, 2002), providing snacks with lower GI values probably cause no harm and possibly reduce the frequency of snacking due to hunger. The contribution of different foods in the meal GI in this study indicated that it may be possible to modify nearly three-quarters of the total glycaemic load by swapping the types of rice/staple and snacks consumed to low-GI alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…satiating than many other foods, including french fries, when served as 1000 kJ portions. According to a review by Anderson and Woodend (2003), high but not low glycaemic responses are associated with increased satiety and/or reduced food intake in the early postprandial phase (1 h) (Holt et al, 1995;Anderson et al, 2002), whereas the reverse occurs in the later phase after a meal (up to 6 h) (van Amelsvoort and Weststrate, 1992). An inverse relationship between glycaemic response and satiety sensation has also been reported, suggesting that low-GI foods are more satiating (Ludwig, 2000;Roberts, 2000), although it has been pointed out that in some of these studies the control of confounding variables was not adequate (Roberts et al, 2002).…”
Section: Energy-equivalent Meals (Study 1)mentioning
confidence: 99%
“…However, the conclusions regarding a potential relationship differ. In a study with isovolumetric beverages, Anderson et al (2002) found that a high glycaemic response was associated with increased satiety in the early postprandial period (1 h). In elderly subjects, mashed potatoes (high-GI food) induced significantly higher glycaemia and satiety compared with a barley meal (low-GI food) containing the same amount of available carbohydrates as measured during 120 min (Kaplan and Greenwood, 2002).…”
Section: Introductionmentioning
confidence: 99%